Implementation Of Biometric-Based Security System On Mobile Banking Application - Saputri, Vettyca Diana (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Security is a crucial aspect in mobile banking applications, given the increasing cyber threats that can harm both users and financial institutions. The implementation of biometric-based security systems, such as fingerprint scanning and facial recognition, offers a more secure solution than traditional authentication methods. This article discusses the implementation of biometric security systems in mobile banking applications, evaluating its effectiveness and challenges in its integration. Using literature review and system prototyping methods, this research shows that biometrics can increase the level of security and convenience for users, but requires attention to privacy issues and technology compatibility.